Study adsorption of cadmium by activated carbon from Mimosa Pigra Linn. - ธรรมโสม ฐิตินันท์ (Progress in Applied Science and Technology, 2017)
The efficiency of cadmium adsorption by activated carbon from Mimosa Pigra Linn. that activated by saturated sodium chloride (NaCl) and potassium hydroxide (KOH) were carried out. The activated carbon were prepared by using the ratio of Mimosa Pigra Linn to saturated sodium chloride 2:1 , shaked with 200 rpm for 24 hours and heated at 773 °C for 95 minutes and the ratio of Mimosa Pigra Linn to potassium hydroxide was 1:1 , shaked with 200 rpm for 24 hours and heated at 400 °C for 180 minutes. The quantity of activated carbon , pH and contact time were studied. The results showed that the optium conditions of activated carbon that activated by NaCl and KOH were activated carbon quantity 80 g/L , contact time 90 minutes and pH 4.5 for carbon that activated sodium chloride and pH 5 for for carbon that activated potassium hydroxide and unactivated carbon.